CALIDAD ECOLÓGICA DEL RÍO VILLETA (Villeta - Cundinamarca) - Ruiz Chavarro, María Victoria; Rincón Hernández, María Eugenia (Tecné, Episteme y Didaxis: TED, 2002)
In this work the composition and the spatial distribution of a community of aquatic insects were studied in order to asses the ecological quailty of ViIIeta River Iocated in the Deparment of Cundinamarca. The hidrologic characteristics of this lotic systerm were also investigated in order search for biotic and abiotic interactions. From February: 1999 to January 2000, samples from two Iocalities were taken monthly and subjected to physicochemical and biological analysis. The most important famlies were Chironomidae (Diptera), Baetidae (Ephemeroptera) and Hydropsychidae (Trichoptera) Both the physicochemical and biological characteristics of this ecosystem are rainfall pattern dependent.